Exploring the effect of the “quaternary regulation” theory of “peripheral nerve-angiogenesis-osteoclast-osteogenesis” on osteoporosis based on neuropeptides - Liu, Shuhua; Chen, Tongying; Wang, Ruolin; Huang, Hongxing; Fu, Sai; Zhao, Yu; Wang, Shihao; Wan, Lei (Frontiers in Endocrinology, 2022)
Osteoporosis is a common bone metabolic disease among the middle-aged and elderly, with its high incidence rate and a major cause of disability and mortality. Early studies found that bone metabolic homeostasis is achieved through osteogenesis-osteoclast coupling. Although these drugs can attenuate bone loss caused by aging, they present specific side effects. With the discovery of CD31hi Emcnhi blood vessels in 2014, the effect of H-type blood vessels on bone metabolism has been valued by researchers, and the ternary regulation theory of bone metabolism of "Angiogenesis-Osteoclast-Osteogenesis" has also been recognized. Nowadays, more studies have confirmed that peripheral nerves substantially impact bone metabolism. However, due to the complex function of peripheral nerves, the crosstalk mechanism of "Peripheral nerve-Angiogenesis-Osteoclast-Osteogenesis" has not yet been fully revealed. Neuropeptide serves as signaling molecules secreted by peripheral nerves that regulate blood vessels, osteoblasts, and osteoclasts' functions. It is likely to be the breakthrough point of the quaternary regulation theory of "Peripheral Nerve-Angiogenesis-Osteoclast-Osteogenesis". Here, we discuss the effect of peripheral nerves on bone osteoporosis based on neuropeptides.